Echocardiography Coupled with Strain Method in the Screening for Cardiac Involvement in Rheumatoid Arthritis - Brahem, Mouna; Amor, Hassen Ibn H.; Sarraj, Rihab; Touil, Imen; Kraiem, Salma; Rouabhia, Ramzi; Hmaier, Ella; Mbarek, Ghassen Haj; Salem, Ameni Ben; Mlouki, Imen; Mhamdi, Sana; Hachfi, Haifa; et al. (Current Rheumatology Reviews, 2024)
Objective: In this study, the usefulness of transthoracic echocardiography (TTE) in systematic screening was assessed for various cardiac abnormalities in patients with rheumatoid arthritis (RA).Methods: We performed a comparative cross-sectional study from July 2020 to February 2021. Each patient underwent a TTE coupled with the strain technique.Results: Seventy-two RA patients and 72 controls were included. Abnormalities detected by TTE were more frequent in RA patients (80.6% vs. 36.1%; p < 0.01), and they were asymptomatic in 65.5% of cases. Valvular involvement was found in 45.8% of RA patients, with a significant difference (p < 0.01). Left ventricular diastolic dysfunction was also more frequent in the RA group (36.1% vs. 13.9%; p < 0.01). Left ventricular systolic dysfunction was absent in our study, but subclinical left ventricular myocardial damage assessed by Global Longitudinal Strain (GLS) method was found in 37.5% of RA patients and 16.6% of controls (p < 0.01). The mean GLS in RA patients was -17.8 ± 2.9 (-22 to -10.7) vs. -19.4 ± 1.9 (-24.7 to -15.7) in controls. Left ventricular hypertrophy was detected in 22.2% of RA patients and in 6.9% of controls (p < 0.01). Pericardial effusion and pulmonary arterial hypertension were present only in the RA group (2.8% of cases). We found a significant relationship between echocardiographic damage and disease activity (p < 0.01), number of painful joints (p < 0.01), functional impact (HAQ) (p = 0.01), CRP level (p < 0.01) and the use and dose of Corticosteroids (p = 0.02; p = 0.01).Conclusion: Echocardiographic damage in RA is frequent and often asymptomatic, hence there has been an increased interest in systematic screening in order to improve the quality of life and vital prognosis of patients. Early management of RA can reduce the risk of occurrence of cardiac involvement.
Keywords: echocardiography